2022
DOI: 10.1155/2022/6260243
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Trends of Research on Anthracycline-Induced Cardiotoxicity from 2002 to 2021: A Twenty-Year Bibliometric and Visualization Analysis

Abstract: Anthracyclines constitute the cornerstone of numerous chemotherapy regimens for various cancers. However, the clinical application of anthracyclines is significantly limited to their dose-dependent cardiotoxicity. A comprehensive understanding of the current status of anthracycline-induced cardiotoxicity is necessary for in-depth research and optimal clinical protocols. Bibliometric analysis is widely applied in depicting development trends and tracking frontiers of a specific field. The present study is aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 122 publications
(124 reference statements)
1
6
0
Order By: Relevance
“…Our data can be traced back to 1990. Our findings are in line with the previously published research (Anuar et al, 2022;Wang et al, 2022;Yang et al, 2022). The first article had been published in 1990.…”
Section: Discussionsupporting
confidence: 93%
“…Our data can be traced back to 1990. Our findings are in line with the previously published research (Anuar et al, 2022;Wang et al, 2022;Yang et al, 2022). The first article had been published in 1990.…”
Section: Discussionsupporting
confidence: 93%
“…(1) Basic information, including title, source, author, and year. (2) Baseline characteristics of the study population, containing the number of trial participants, age, and disease type. (3) Intervention details and follow-up time.…”
Section: Methodsmentioning
confidence: 99%
“…However, dose-dependent cardiotoxicity always significantly limited the clinical application of anthracyclines ( 1 ). Research reported that cumulative doxorubicin doses of 400, 550, and 700 mg/m 2 could increase the incidence of congestive heart failure by 4.7%, 26%, and 48% ( 2 ). The cumulative toxic effect on the heart will affect oncology patients' prognosis of seriously ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, no anthracycline equivalent has been shown to work better than doxorubicin. Anthracycline liposomal formulations are currently the best-known way to improve the index and spectrum of action of regular anthracyclines with less cardiotoxicity [82]. The existence of quinone moiety in the structure of anthracycline rings is of great clinical value as it takes part in redox reactions that lead to highly reactive chemical species, which are mainly considered the cause of anthracycline-induced cardiotoxicity [83].…”
Section: Anthracyclinesmentioning
confidence: 99%